Bacterial Nanocellulose Loaded with Bromelain: Assessment of Antimicrobial, Antioxidant and Physical-Chemical Properties. Issue 1 (December 2017) - Ataide, Janaína; Carvalho, Nathália; Rebelo, Márcia; Chaud, Marco; Grotto, Denise; Gerenutti, Marli; Rai, Mahendra; Mazzola, Priscila; Jozala, Angela
Abstract Bacterial nanocellulose (BNC) has desirable properties for wound healing such as high purity, good shape retention, and high water binding capacity. Bromelain is a protease found in pineapple tissues and has been applied in several fields, it has anti-inflammatory and anticancer properties, promotes cell apoptosis, amongst others. In this work, a BNC based device for the controlled release of bromelain was developed. BNC were submersed in sterilized bromelain solution and incubated at 25 °C under 100 rpm for 24 h. Physical-chemical properties, protein concentration, antioxidant and antimicrobial activities were measured. Results demonstrate that BNC could improve bromelain antimicrobial activity 9 times. Those findings allow concluding that bromelain is a promising molecule to be incorporated into BNC's. The BNC's characteristics seem to represent a new promising delivery system of the loaded biomolecule, and protected from external actions.